Pengaruh Kualitas Pelayanan dan Kepuasan Pasien terhadap Loyalitas Pasien di Rumah Sakit Puangrimaggalatung Sengkang Kabupaten Wajo - Asrul Jaya (Jurnal Pustaka Cendekia Pendidikan, 2024)
Satisfaction is achieved when quality meets and exceeds customer expectations, desires and needs. On the other hand, if quality does not meet and exceed customer expectations, desires and needs, satisfaction will not be achieved. Patient satisfaction will influence patient loyalty to use the services of Puangrimaggalatung Hospital, Wajo district. The aim of this research is to determine the influence of service quality and satisfaction on patient loyalty at Puangrimaggalatung Sengkang Hospital, Wajo Regency. This research method is quantitative observational analytic with a cross sectional approach, with a sample size of 92 respondents. The sampling technique uses accidental sampling. The statistical analysis used is Multiple Linear Regression. The research results show that service quality has a positive and significant effect on patient loyalty at Puangrimaggalatung Sengkang Hospital, Wajo Regency. Likewise, patient satisfaction has a positive and significant effect on patient loyalty at Puangrimaggalatung Hospital, Wajo Regency. Simultaneously, service quality and patient satisfaction have a positive and significant effect on patient loyalty at Puangrimaggalatung Sengkang Hospital, Wajo Regency.